Perbandingan Kekuatan Genggaman Tangan dan Kekuatan Tubuh Bagian Atas antara Individu yang Tidak Banyak Bergerak dan Pemanah - Jiun Sien Lau; Muhammad Mustaqim Jariah; Rosniwati Ghafar; Erie Zuraidee Zulkifli; Nur Syamsina Ahmad (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose: Muscular strength is crucial for performing daily tasks and enhancing sports performance. However, limited research has compared the handgrip and upper body strength between sedentary individuals and archers. This study aimed to compare the handgrip and upper body strength between the sedentary individuals and archers. Materials and methods: A cross-sectional study design was employed, involving youth archers of Kelantan Sports Council (n=20; Mean age:14.7±1.22 years old) and sedentary individuals from Kelantan secondary school (n=20; Mean age:14.8±1.15 years old). Participants were selected using purposive sampling. Participants’ handgrip strength of dominant and non-dominant arms was measured using a hand dynamometer, while the upper body strength was measured via medicine ball throw test. All the tests were conducted for 3 trials; the average of the trials was used the analysis using Mann-Whitney test. Results: There was a significant difference (p<0.05) in the comparison of handgrip strength for both arms between the groups. Archers exhibited higher dominant handgrip strength (32.5±4.1 kg) than sedentary individuals (25.8±3.9 kg). Similarly, upper body strength demonstrated a significant difference (p<0.05), with archers achieving a longer medicine ball throw distance (5.4±0.6 m) than sedentary individuals (4.1±0.5 m). Conclusions: To conclude, archers possess greater handgrip and upper body strength than sedentary individuals, highlighting the positive impact of archery training on muscular strength development.